Stabilitas Dan Ukuran Partikel Mikroemulsi Minyak Atsiri Sereh (Cymbopogon Citratus) Dengan Rasio Surfaktan Dan Ko-Surfaktan - Putra, Anak Agung Gede Surya Pradana; Suhendra, Lutfi; Anggreni, Anak Agung Made Dewi (Department of Agroindustrial Technology, Faculty of Agricultural Technology, Udayana University, 2025)
Lemongrass essential oil, derived from the Cymbopogon citratus plant, is a highly beneficial essential oil widely used in the pharmaceutical, food, and cosmetic industries. Microemulsions are colloidal systems consisting of two immiscible phases, namely the oil phase and the water phase, stabilized by surfactants and co-surfactants. This study aims to evaluate the effect of the surfactant and co-surfactant ratio on the characteristics of lemongrass essential oil microemulsions and to determine the optimal formulation ratio that produces the best microemulsion. In this study, 11 different surfactant and co-surfactant ratio variations were used, with each treatment being tested twice, resulting in a total of 22 experimental units. The analysis results indicated that the surfactant and lemongrass essential oil mixture ratio had a highly significant effect (P<0.05), with the obtained variance values falling below the thresholds of 0.01 and 0.05. The research data revealed that the best lemongrass essential oil microemulsion formulation was achieved at a 60:40 ratio, with an index value of 0.144±0.005 and a transmission value of 87.07±0.820244. After centrifugation, the index was 0.061±0.008, with a transmission value of 95.907±1.53017, resulting in a transparent appearance with a slightly sticky texture.